An Innovative Additively Manufactured Design Concept of a Dual-Sided Cooling System for SiC Automotive Inverters - Ekaterina E. Abramushkina; Gamze Egin Martin; Atila Sen; Shahid Jaman; Haaris Rasool; Mohamed El Baghdadi; Omar Hegazy (IEEE Access, 2024)
Modern Electric Vehicles (EVs) require high power and high efficient powertrains to extend their power range. A key element of the electric powertrain is its drive with an electric motor controlled by a traction inverter. A cooling system dissipates heat generated due to the losses in this inverter and keeps its temperature within limits, i.e. below the operational maximum value. Indirect cooling systems are often the preferred solution due to their easy implementation and robust separation of the electric/electronic parts and the coolant circuit. Indirect cooling comes with additional surface interfaces, hence thermal barriers and increased thermal resistance for the losses’ heat flow path. One way to increase the system’s heat transfer coefficient is by implementing power electronics with dual-sided cooling (DSC) solutions and by enhancing surface structures for the cold plates. Manufacturing complex cold plate solutions with internal surface-enhancing structures by way of classical techniques (e.g. aluminum extrusion with CNC machining) can be difficult, costly, or even not possible. Sealed one-piece solutions are preferred, without the need to weld parts or to use screws, glue, gaskets, etc. 3D metal printing allows to manufacture of a one-unit compact, light, and reliable cold plate. This study shows the advantages and limitations of a 3D metal-printed inverter cold plate by presenting the microchannel design, numerical thermal simulations, and experimental results for the liquid cooled DSC SiC and Si inverters. This work explores the compatible use of 3D metal printing solutions, which will aid the development of modern high-power density EVs.